Digital platform for shared solutions and open innovations: proposal of a structured theoretical model - de Oliveira, Antônio Honorato [UNESP] (University Nove de Julho, 2024)
Objective: This article aims to present a collaborative digital platform model, structured to promote the improvement of communications, integration, and cooperation between the agents of the Triple Helix (TH), in the construction of shared solutions and open innovations activities. Project / method / approach: The e-Delphi method applied in this research is directed to identify levels of consensus and dissent among respondents, when asked about the validation of the proposed platform model. Main results: The main results show that the Content Validity Index, the Coefficient of Variation, and the Interquartile Range, were consistent with the recommended standard (Okoli & Pawlowski, 2004; Polit & Beck, 2006; Alexandre & Coluci, 2011 and Miguel, 2012). Research limitations / implications: The insertion of facilitating instruments in endogenous communication and integration processes can contribute to the effectiveness of the TH model. The model is proposed in its theoretical form, as an academic contribution, and the requirements for construction are provided in this document. Originality / value: The relevance of this article is corroborated by the unprecedented application of the calculation of three statistical indicators (CVI-CV-IR) in research using the e-Delphi method, and for the unprecedented proposition of a digital platform model for shared solutions and open innovations. Social / management contributions: As a scientific contribution, the platform can contribute to improving cooperation between institutions of the Triple Helix model, especially in activities involving shared solutions and open innovations. The proposed model can be replicated, safeguarding the necessary adaptations to different regional realities.
Plataforma digital para soluciones compartidas e innovaciones abiertas: propuesta de un modelo teórico estructurado
Plataforma digital para soluções compartilhadas e inovações abertas: proposta de um modelo teórico estruturado
Keywords: digital platforms; e-Delphi method; open innovation; shared solutions; triple helix model